Multiple Passive Optical Network (PON) network design with unconstrained splitting stages - L. Gouveia; Lopes, M. J.; Sousa, A. (IO2015 - XVII Congresso da APDIO, 2015)
A PON is a network technology for deploying access networks based on passive optical components. In a PON access network, the client terminals are connected to a Central Office through optical splitters and interconnecting fibers where each splitter splits the input optical signal coming from the Central Office over its different output ports. We consider a PON topology where the splitting ratio and the number of splitting stages is not constrained but, instead, are decided based on the cost of the network solution. We present ILP models and propose heuristics to obtain feasible solutions.